Estimating Fuzzy hazard Rate Function of Generalized Exponential Distribution - A. Ibrahim, Nathier (Opción, 2019)
the paper deals with estimating two parameters (β,α) of generalized exponential failure model, then comparing fuzzy hazard rate function model, the methods of estimation are, moments, maximum likelihood, and proposed one, depend on frequency ratio method were it is derived according to studied dis- tribution, then used for estimation parameters (β,α).